G-quadruplex motif at the 3' end of sgRNAs improves CRISPR-Cas9 based genome editing efficiency - Nahar, Smita; Sehgal, Paras; Azhar, Mohammad; Rai, Manish; Singh, Amrita; Sivasubbu, Sridhar; Chakraborty, Debojyoti; Maiti, Souvik (Chemical Communications, 2018)
Originating as a component of prokaryotic adaptive immunity, the type II CRISPR/Cas9 system has been repurposed for targeted genome editing in various organisms. Although Cas9 can bind and cleave DNA efficiently under in vitro conditions, its activity inside a cell can vary dramatically between targets owing to differences between genomic loci and availability of enough Cas9/sgRNA (single guide RNA) complex molecules for cleavage. Most methods to improve CRISPR/Cas9 activity have so far relied on Cas9 protein engineering or base modifications in the sgRNA sequence. Here we demonstrate that a structure based rational design of sgRNAs can enhance the efficiency of Cas9 cleavage in vivo. By appending a naturally forming RNA G-quadruplex motif to the 3′ end of sgRNAs we can improve its stability and target cleavage efficiency in zebrafish embryos without inducing off-target activity, thereby underscoring its value in the design of better and optimized genome editing triggers.